Does the use of i-FACTOR bone graft affect bone healing in those undergoing periacetabular osteotomy (PAO) for developmental dysplasia of the hip (DDH)? A retrospective study. Issue 3 (28th June 2022) - O'Brien, Michael J M; Jones, Denise M; Semciw, Adam Ivan; Balakumar, Jitendra; Grabinski, Rafal; Roebert, Justin; Coburn, Georgia M; Mechlenburg, Inger; Kemp, Joanne L
ABSTRACT: The aims of this study were to compare, in patients with and without the use of i-FACTOR bone graft during periacetabular osteotomy (PAO) surgery for developmental dysplasia of the hip (DDH), (i) bone healing at six-weeks post-operatively (ii) rate of complications. This was a retrospective review of case records. Participants were people aged 15-50 years undergoing rectus-sparing minimally invasive PAO surgery for DDH. Group 1: patients with i-FACTOR, Group 2: No i-FACTOR. The primary outcome was the rate of bone healing on radiographs at 6 weeks. The likelihood of bone healing was compared using logistic regression with Generalised Estimating Equations (GEE) and expressed as odds ratios (95% confidence intervals (CIs; P  < 0.05)). The occurrence of complications was extracted from surgical records. The i-FACTOR group had 3-times greater odds of partial/full union than those without [adjusted odds ratio (95% CIs, P -value)]: [3.265 (1.032 to 10.330, P  = 0.044)]. The i-FACTOR group had 89% partial/full union at 6-weeks, compared to 69% of the non-i-FACTOR group. Half of the patients had leaking of bone graft in the i-FACTOR group versus 10% in the non-i-FACTOR group, 26% of the i-FACTOR group and 12% of the non-i-FACTOR group had neuropraxia of the lateral femoral cutaneous nerve (LFCN). Complication rates were low, and similar between groups. However, the rate of LFCN neuropraxia and bone graft leakage was higher in the i-FACTOR. These findings should be confirmed in a future prospective randomised clinical trial and include outcomes such as pain and quality of life.